Rhizobial benefits to an herbaceous invader depend on context and symbiotic strain - Ramula Satu; Mousavi Seyed Abdollah; Kalske Aino (SPRINGER, 2025)
Background and aims: For invasive plant species that associate with mutualistic symbionts, partner quality can be critical to their invasion success. This might be particularly true for legumes that host nitrogen-fixing bacteria (rhizobia). Here, we examined the relative effectiveness of rhizobial strains on the invasive legume Lupinus polyphyllus.
Methods: We isolated rhizobia from field populations of L. polyphyllus and conducted inoculation experiments in which we quantified plant growth in greenhouse and common-garden conditions.
Results: Differences in nodulation and effectiveness in terms of increasing plant growth among rhizobial strains of the genus Bradyrhizobium were more pronounced in the greenhouse than in the common garden. All six rhizobial strains nodulated the host plant in greenhouse conditions, but one failed to nodulate in the common garden. Under greenhouse conditions, five rhizobial strains increased plant biomass by 66-110%, while one provided negligible benefits compared to control plants without rhizobia, suggesting that rhizobial identity might be critical to the invader's performance. However, the common-garden experiment revealed no differences in the effectiveness of rhizobial strains in terms of plant biomass, number of leaflets per leaf, height, root:shoot ratio, or survival. Moreover, the performance of rhizobia-inoculated plants in the common garden did not differ from plants without rhizobia, which may call into question the fitness benefits of rhizobia to field populations of this species.
Conclusions: The discrepancies observed between the two environments highlight the importance of considering field-realistic growing conditions and multiple plant traits when assessing the potential growth benefits of symbiotic partners to host plants.